Collaborative fashion consumption and slow fashion: paths to sustainable fashion (ModaPalavra e-periódico, 2021)
This study discusses the possibility of integration between collaborative fashion consumption and slow fashion, suggesting that the demand for sustainability in fashion can be met through the benefits arising from the acquisition of exchanged, rented, second-hand, vintage or recycled, allied to the slow movement. As a methodological approach, the study emerges from the appropriation of literature on the themes of collaborative consumption of fashion and slow fashion, presenting reflections and articulations on the subjects. As a result, there is evidence that the themes make up the field of sustainable fashion, configuring an alternative for consumers who wish to enter this fashion segment. The main contributions of this study lie in the presentation of propositions and considerations that can serve as a framework for the development of future research in the field of sustainable fashion.
Keywords: sustainable fashion; collaborative fashion consumption; slow fashion